2021
DOI: 10.21203/rs.3.rs-154409/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined Management can Decrease Blood Pressure: A Health-seeking Behaviors Investigation among Hypertensive Patients in Urban Communities in China

Abstract: Background: Hypertensive patients can freely choose the informal medical facilities such as pharmacies, community health service centers, and cardiology clinics in secondary or tertiary hospitals, as the routine places for medical treatment in China at present. It is not clear the proportion, influencing factors and the effects on blood pressure (BP) of different health-seeking behaviors among hypertensive patients in urban communities. The aim of the study is to investigate the health-seeking behaviors and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Among them, the level of education had a positive effect on outpatient visits in the chronic disease population. It has also been previously reported that the level of education is related to patients' healthcare behaviors, and the higher the level of education, the higher the likelihood of patients choosing highlevel hospital visits [30]. Our ndings suggest that age, sex, self-assessed health status, hukou type, monthly income, health insurance, and residence type in uence patients' hospitalization and medical care.…”
Section: Factors Affecting Access To Health Care For the Chronically Illsupporting
confidence: 76%
“…Among them, the level of education had a positive effect on outpatient visits in the chronic disease population. It has also been previously reported that the level of education is related to patients' healthcare behaviors, and the higher the level of education, the higher the likelihood of patients choosing highlevel hospital visits [30]. Our ndings suggest that age, sex, self-assessed health status, hukou type, monthly income, health insurance, and residence type in uence patients' hospitalization and medical care.…”
Section: Factors Affecting Access To Health Care For the Chronically Illsupporting
confidence: 76%